Sistem Informasi Manajemen Pelayanan Desa Berbasis Web di Desa Lebani Kecamatan Belopa Utara - Muhammad Kasran; Sofyan Syamsuddin; Sahrir Sahrir; Khoirun Nisa (Jurnal PkM (Pengabdian kepada Masyarakat), 2023)
The rapid development of technology is very influential on community service in the village area. Therefor Lebani Village, Belopa Utara sub district, Luwu Regency has made various improvements, including one of them is an increase in the information system. The current condition of the population administration service system in the village is still conventional or manual, such as: (a) Village population recording data in register book; (b) Archival data collection, especially correspondence, has not implemented an application-based information system. This has an impact on both village officials and villagers, where human error often occurs, queues for sevice, and a waste of time and money. Therefore we need a system to solve the existing problems. Based on this problem, community service inplementers develop a Village Service Management Information System (SIMPEDA)to facilitate population data service and administration. It is hoped that by using empowement, and support village operational costs. The service implementation program is divided into thee stages, namely the socialization stage, the village management infomation system training stage, and the monitoring and evaluation stage.